1973
DOI: 10.2172/4460258
|View full text |Cite
|
Sign up to set email alerts
|

DOMINO, a general purpose code for coupling discrete ordinates and Monte Carlo radiation transport calculations

Abstract: A. sethod of coupling two-dimensional discrete oriinates calculations with Mcnte Carlo calculations is incorpcr&ted in •Uie MEiO code. In particular, DOT, a tvo-dimensional discrete ordinates code, has been coupled with MORSE, a Monte Carlo code. The discrete ordinates calculation is limited to an r-z geceetry. Either the DOT boundary angular fivxec or the angular fluxes at internal surfaces say be input to DOMINO. Any amount of su.-face inay be used in DOMINO; i.e., frori all aesh intervals down to a portion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The angular neutron flux obtained by the two-dimensional design analysis was applied to the incident source at the radial inner boundary. It was converted to probability distribution source for MORSE-CG with use of DOMINO 7) code. The bottom boundary source was omitted because the result of design analysis showed that neutrons at the bottom level flew to the slant downward direction and further the bottom level was located at 5 m down from the bottom of DHX's.…”
Section: Condition For Three-dimensional Calculationmentioning
confidence: 99%
“…The angular neutron flux obtained by the two-dimensional design analysis was applied to the incident source at the radial inner boundary. It was converted to probability distribution source for MORSE-CG with use of DOMINO 7) code. The bottom boundary source was omitted because the result of design analysis showed that neutrons at the bottom level flew to the slant downward direction and further the bottom level was located at 5 m down from the bottom of DHX's.…”
Section: Condition For Three-dimensional Calculationmentioning
confidence: 99%
“…It is also seen from the Tokyo proceedings and those of the 1984 Topical on Reactor Physics*and Shielding at Chicago^ that Monte Carlo analysis of any realistic system is often coupled with some other calculation methoddiscrete ordinates, diffusion theory, point kernel, or a separate Monte Carlo calculation, A much used scheme has been the DOT-DOMINO-MORSE 24…”
Section: Other Aspects Of Deep Penetration Calculations * ~ a Faimentioning
confidence: 99%